An audio processing pipeline for acquiring diagnostic quality heart sounds via mobile phone. (June 2022) - Shariat Panah, Davoud; Hines, Andrew; McKeever, Joseph A.; McKeever, Susan
Abstract: Recently, heart sound signals captured using mobile phones have been employed to develop data-driven heart disease detection systems. Such signals are generally captured in person by trained clinicians who can determine if the recorded heart sounds are of diagnosable quality. However, mobile phones have the potential to support heart health diagnostics, even where access to trained medical professionals is limited. To adopt mobile phones as self-diagnostic tools for the masses, we would need to have a mechanism to automatically establish that heart sounds recorded by non-expert users in uncontrolled conditions have the required quality for diagnostic purposes. This paper proposes a quality assessment and enhancement pipeline for heart sounds captured using mobile phones. The pipeline analyzes a heart sound and determines if it has the required quality for diagnostic tasks. Also, in cases where the quality of the captured signal is below the required threshold, the pipeline can improve the quality by applying quality enhancement algorithms. Using this pipeline, we can also provide feedback to users regarding the cause of low-quality signal capture and guide them towards a successful one. We conducted a survey of a group of thirteen clinicians with auscultation skills and experience. The results of this survey were used to inform and validate the proposed quality assessment and enhancement pipeline. We observed a high level of agreement between the survey results and fundamental design decisions within the proposed pipeline. Also, the results indicate that the proposed pipeline can reduce our dependency on trained clinicians for capture of diagnosable heart sounds. Highlights: A quality assessment and enhancement pipeline for heart sound signals captured by mobile phones is proposed. Survey of a group of clinicians was conducted to inform and validate the pipeline design decisions. The survey results confirm the validity of the fundamental design decisions within the proposed pipeline. The proposed pipeline can reduce our dependency on clinicians to capture diagnostic quality heart sounds using mobile phones.